Stability of betanin in pitaya powder and confection as affected by resistant maltodextrin - Shaaruddin, Safura; Mohd Ghazali, Hasanah; Mirhosseini, Seyed Hamed; Muhammad, Kharidah (Elsevier, 2017)
Physicochemical properties and stability of betanin in pitaya juice spray dried with maltodextrin (MDp) and resistant maltodextrin (RMDp), and its stability after incorporation into sugar confection were assessed. MDp exhibited more favorable powder properties with higher betanin retention, compared to RMDp. Morphology of MDp exhibited well defined spheres as compared to RMDp which displayed agglomerated particles. Storage for 3 months at 4 °C, 25 °C and 40 °C exhibited higher betanin degradation in RMDp at all temperatures with corresponding lower half-lives compared to MDp. Exposure of powder to light increased degradation of betanin in RMDp more so than in MDp. In sugar confection, RMDp exhibited higher betanin retention post processing at 78.13% compared to MDp at 69.06%. However, after storage for 3 months at 25 °C and 40 °C, stability of betanin in candies incorporated with RMDp reduced below that of candies incorporated with MDp, signifying higher stability in the latter.